0230 Preimmunization With a Non-pathogenic Bacterium Mycobacterium vaccae NCTC11659 Prevents the Development of Cortical Hyperarousal and a PTSD-like Sleep Phenotype Following Sleep Disruption Plus Acute Stress in Mice. (12th April 2019) - Bowers, Samuel J; Lambert, Sophie; He, Shannon; Olker, Christopher J; Song, Eun Joo; Wright, Kenneth P; Fleshner, Monika; Lowry, Christopher A; Turek, Fred W; Vitaterna, Martha H
Abstract: Introduction: Because regular sleep disruption can increase vulnerability to stress-related psychiatric disorders, there is a need to explore novel countermeasures to increase stress resilience after inadequate sleep. Immunization with heat-killed Mycobacterium vaccae NCTC11659 (MV), an environmental bacterium and immunomodulator, can increase resilience to chronic stress in mice. We therefore tested the hypothesis that MV immunization would prevent the negative impacts of five days of sleep disruption on stress-induced changes in sleep in mice. Methods: 120 male C57BL/6N mice were implanted with EEG/EMG recording devices and given 3 weekly injections of either MV or vehicle before entering the experimental protocol (day 0). On days 1-5, sleep was disrupted by a slowly rotating bar, with an ad libitum sleep opportunity from ZT2-ZT6. At ZT4 of day 5, mice were exposed to a 1-hour episode of social defeat stress. Sleep recording continued for seven days after social defeat (day 12). Groups received just sleep disruption, just social defeat, both ('double hit'), or neither. Results: In vehicle-treated mice receiving just social defeat, an increase in NREM delta (0.5-4Hz) power compared to baseline was observed during the post-stress dark period (p=0.005, Wilcoxon signed rank test). However, this was absent in mice receiving the double hit, who instead had elevated power in the high frequency beta (15-30Hz) power band in both NREM (p=0.002) and REM (p=0.001). Mice receiving the double hit also had increased REM and sleep fragmentation compared to controls for at least 6 days post-stress (p<0.05, ANOVA). NREM beta power immediately post-stress correlated with REM sleep disturbances 6 days later. MV preimmunization prevented all double hit-induced sleep disturbances. Conclusion: These results suggest repeated sleep disruption may increase vulnerability to an acute stressor in part by shifting the adaptive increase in delta power to a maladaptive increase in beta power during post-stress sleep. Importantly, these data provide further evidence supporting microbiota-based countermeasures to promote health. Support (If Any): Office of Naval Research Grant #N00014-15-1-2809; NIH Training Grant T32HL007909